« This » comme marqueur privilégié du genre : le cas des résumés de thèses - Geneviève Bordet (Discours)
The ever-increasing impact of academic publishing has made genre analysis a priority, since it defines the requirements of the communicative goals inside a specific community. This study aims at exploring how the reference marker “this” contributes to making the PhD abstract a recognizable type of genre and as such likely to fulfil its objectives. “This”, as a rhetorical device, seems particularly adapted to a type of discourse characterized by its distinctive conciseness and highly symbolic status in the academic field. Our corpus includes abstracts from five disciplines, written in English by English and French-speaking doctoral students. This provides evidence for establishing a typology of the functions of “this” which create focalisation, and hence determine a rhetorical strategy. The exophoric “this” establishes the link between the abstract and its context of enunciation while its endophoric uses create the dynamics of the focus structure, ranging from a simple repetitive anaphor to a shift or encapsulation of the reference. The application of this classification to a corpus of abstracts in the fields of mathematics education and materials science highlights an array of rhetorical strategies depending on the writer’s disciplinary and linguistic origin. We argue that the mastering of the interpretive space provided by the use of “this” helps the PhD candidate to demonstrate his/her legitimacy and authority, therefore contributing to his/her admission inside the academic community.